Lymphotoxin-sensitive microenvironments in homeostasis and inflammation - Boulianne, Bryant; Porfilio, Elisa A.; Pikor, Natalia; Gommerman, Jennifer (Frontiers in Immunology, 2012)
Stromal cell micro-microenvironments within lymphoid tissues are designed to support immune cell homeostasis and to regulate ongoing immune responses to pathogens. Such stromal cell networks have been best characterized within lymphoid tissues including the spleen and peripheral lymph nodes, and systems for classifying stromal cell phenotypes and functions are emerging. In response to inflammation, stromal cell networks within lymphoid tissues change in order to accommodate and regulate lymphocyte activation. Local inflammation in non-lymphoid tissues can also induce de novo formation of lymphoid aggregates, which we term here "follicle-like structures". Of note, the stromal cell networks that underpin such follicles are not as well characterized and may be different depending on the anatomical site. However, one common element that is integral to the maintenance of stromal cell environments, either in lymphoid tissue or extra-lymphoid sites, is the constitutive regulation of stromal cell phenotype and/or function by the Lymphotoxin (LT) pathway. Here we discuss how the LT pathway influences stromal cell environments both in homeostasis and in the context of inflammation in lymphoid and non-lymphoid tissues.